Afatinib in patients with metastatic or recurrent HER2-mutant lung cancers: a retrospective international multicentre study. (March 2019) - Lai, W. Victoria; Lebas, Louisiane; Barnes, Tristan A.; Milia, Julie; Ni, Ai; Gautschi, Oliver; Peters, Solange; Ferrara, Roberto; Plodkowski, Andrew J.; Kavanagh, John; Sabari, Joshua K.; Clarke, Stephen J.; et al.
Abstract: Introduction: HER2 mutations occur in 1–3% of lung adenocarcinomas. With increasing use of next-generation sequencing at diagnosis, more patients with HER2 -mutant tumours present for treatment. Few data are available to describe the clinical course and outcomes of these patients when treated with afatinib, a pan-HER inhibitor. Methods: We identified patients with metastatic or recurrent HER2 -mutant lung adenocarcinomas treated with afatinib among seven institutions across Europe, Australia, and North America between 2009 and 2017. We determined the partial response rate to afatinib, types of HER2 mutations, duration of response, time on treatment, and survival. Results: We collected information on 27 patients with stage IV or recurrent HER2 -mutant lung adenocarcinomas treated with afatinib. Of 23 patients evaluable for response, three partial responses were noted (13%, 95% confidence interval [CI] 4–33%). In addition, 57% of patients (13/23) had stable disease, and 30% (7/23) had progressive disease. We documented partial responses in patients with HER2 exon 20 insertions, including two with YVMA insertion and one with VAG insertion. Two patients with partial responses were previously treated with trastuzumab and pertuzumab. Median duration of response to afatinib was 6 months (range 5–10); median time on treatment was 3 months (range 1–30) and median overall survival from the date of diagnosis of metastatic or recurrent disease was 23 months (95% CI 18–53 months). Conclusions: Afatinib is modestly active in patients with HER2 -mutant lung adenocarcinomas, including responses after progression on prior HER2-targeted therapies. However, investigations into the biology of HER2 -mutant lung adenocarcinomas and development of better HER2-directed therapies are warranted. Highlights: The response rate of advanced HER2 -mutant lung cancers treated with afatinib was 13%. All responses were seen in patients with HER2 exon 20 insertion mutations. Responses were observed even in patients treated with prior HER2-targeted therapies. Afatinib led to durable disease control in a subset of patients (up to 30 months). Afatinib was well tolerated in most patients.